Evaluation of Some Neurotransmitters and Oxidative Stress by Manganese Chloride After Treatment with Lavender Ethanolic Extraction in Male Rats - Ashwaq Jabbar Almiahy; Athraa Shakir Dakhil (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This search intended to speculate the role of lavender ethanolic extract by reducing the toxicity of manganese in male rats. 32 white male Norwegian rats were divided into 4 equal groups. Group 1: as a control group left without treatments (only 1 ml of distilled water/ animal/ day). Group 2: were dosed manganese chloride at a concentration of 100 mg/ kg b.w. / day. Animals in Group 3 and Group 4 were dosed Manganese chloride at a concentration of 100 mg/kg b.w. then lavender ethanolic extract at a concentration of 200 and 400 mg/kg respectively, all by oral gavages and treated daily for six weeks. Then the next criteria were investigated: Neurotransmitters (dopamine and Ach (acetylcholine) in the mid brain) serotonin in serum. Oxidation indicators (glutathione and malondialdehyde in the brain and superoxide dismutase and catalase in serum). The results exhibited in both groups 3 and 4 there were a significant decrease in the concentrations of Ach accompanied by a significant increase in levels of dopamine and serotonin, also return levels of MDA (Malondialdehyde) to normal, as well as a significant increase in GSH (Glutathione) concentrations in rats mid brain. Moreover, the significant rising of SOD (Superoxide dismutase) and CAT (Catalase) levels in serum of rats in these groups indicated a noticeable improvement was achieved by lavender ethanolic extraction as compared to group 2. Conclusion, the antioxidant and antitoxic activity of lavender ethanolic extract promises in grate achievement in various health fields, including medicine, food industries and cosmetics.